Cultural Values of Javanese Manners in Javanese Language Subjects in an Effort to Strengthen the Profile of Pancasila Students in Madrasah Ibtidaiyah - Noptario; Irawan, M. Ferry; Rizki, Nikentari (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
The rapid influx of globalisation that reaches millennials and gen z, the next generation of Indonesia, certainly has a negative impact that must be dealt with. One of the negative impacts is that local cultures are increasingly abandoned and forgotten, to answer these problems, of course, must use a special strategy so that students in schools understand and can apply local cultures. The Pancasila student profile is one of the flagship programmes in the Merdeka curriculum which aims to shape student character, one of the themes contained in the Merdeka curriculum is the theme of local wisdom which discusses local cultures, so it is hoped that it can help students understand the values in local culture in their area. This research uses a qualitative research approach with a field research method. Data collection techniques in this study used interviews and previous research as references and reinforcements. While the data analysis technique uses miles and hubermans theory with data condensation, data presentation, conclusion drawing and verification. The values in Javanese manners culture consist of the value of respect and courtesy, the value of Silih asih, silih asah and silih asuh, the value of speaking ethics and the value of simplicity. The four values can be obtained by students through the project of strengthening the profile of Pancasila students on the theme of local wisdom, so it is hoped that the Javanese manners culture taught in Javanese language subjects is expected to help strengthen the profile of Pancasila students.